Screening of Phytochemical Secondary Metabolites of Muntingia Calabura: a Potential as Hepatoprotector - Elasari Dwi Pratiwi; Niluh Puspita Dewi (Journal of Fundamental and Applied Pharmaceutical Science, 2022)
Muntingia calabura is one of the plants employed to produce herbal-based treatments. Muntingia calabura leaves are traditionally used as an alternative medicine due to their secondary metabolites. The maceration method extracted Muntingia calabura leaves using 96% ethanol solvent for 3 x 24 hours. The fractionation process was carried out using a separating funnel method with different polarities, such as n-hexane, ethyl acetate, and ethanol-water. Thin-layer chromatography (TLC) was used to confirm the phytochemical screening. TLC conditions under UV light 254 and 366 nm using solvents, such as chloroform: methanol (alkaloids), butanol: acetic acid: water (flavonoids), chloroform:methanol: water (saponins), and chloroform: methanol (phenolic). The phytochemical screening results of extracts and Muntingia calabura fractions contained secondary metabolites, such as alkaloids, flavonoids, tannins, saponins, and phenolics. TLC results showed that n-hexane fraction contained flavonoid and saponin compounds; ethyl acetate fraction contained alkaloids, flavonoids, saponins and phenolic compounds; and ethanol-water fraction contained alkaloids, flavonoids, saponins, and phenolics. Muntingia calabura leaves indicated the potential as herbal medicine by containing secondary metabolites.